PENGARUH PROMOSI PENJUALAN DAN KUALITAS PELAYANAN TERHADAP MINAT BELI KONSUMEN TOYOTA VIOS PADA UNIT USAHA PT. AGUNG TOYOTA AUTOMALL CABANG DURI - Hutagalung, Jordan Roman Riquelme; Othman, Lie (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The level of competition in the automotive industry in Indonesia is currently very tight, so every automotive company is always trying to innovate in creating a product that is popular with the public. Sales promotion is a marketing activity which is communication carried out by a company to buyers or consumers which includes news, persuasion and influences everything regarding the goods or services produced for consumers. This research aims to explain the relationship and influence of the Sales Promotion and Service Quality variables on Consumer Purchase Interest. This type of research is quantitative research. The population used in this research is Toyota Vios car consumers at PT. Toyota Agung Automall Duri, totaling 129 people with a sample of 97.55 people. The results of this research are that there is a significant influence of sales promotion on consumer buying interest in Toyota Vios at PT. Agung Toyota Automall Duri Branch. There is a significant influence of service quality on consumer buying interest in Toyota Vios at PT. Agung Toyota Automall Duri Branch. There is a significant influence of sales promotion and service quality on consumer buying interest in Toyota Vios at PT units. Agung Toyota Automall Duri Branch. Keywords: Automotive Industry, Quality, Purchase Interest, Promotion.